2016
DOI: 10.3758/s13428-016-0747-8
|View full text |Cite
|
Sign up to set email alerts
|

“Going to town”: Large-scale norming and statistical analysis of 870 American English idioms

Abstract: An idiom is classically defined as a formulaic sequence whose meaning is comprised of more than the sum of its parts. For this reason, idioms pose a unique problem for models of sentence processing, as researchers must take into account how idioms vary and along what dimensions, as these factors can modulate the ease with which an idiomatic interpretation can be activated. In order to help ensure external validity and comparability across studies, idiom research benefits from the availability of publicly avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…For various languages, such as English (Titone and Connine, 1994;Libben and Titone, 2008;Bulkes and Tanner, 2017;Nordmann and Jambazova, 2017), French (Caillies, 2009;Bonin et al, 2013Bonin et al, , 2017, German (Citron et al, 2016), Italian (Tabossi et al, 2011) and Chinese (Li et al, 2016), norms have been published with the aim to increase the reliability of stimulus material in psycholinguistic studies on idioms. These norms provide a number of interesting measures, such as familiarity, decomposability, predictability or emotional valence, for several hundreds of items per language.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For various languages, such as English (Titone and Connine, 1994;Libben and Titone, 2008;Bulkes and Tanner, 2017;Nordmann and Jambazova, 2017), French (Caillies, 2009;Bonin et al, 2013Bonin et al, , 2017, German (Citron et al, 2016), Italian (Tabossi et al, 2011) and Chinese (Li et al, 2016), norms have been published with the aim to increase the reliability of stimulus material in psycholinguistic studies on idioms. These norms provide a number of interesting measures, such as familiarity, decomposability, predictability or emotional valence, for several hundreds of items per language.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, idiom norming studies traditionally do not take this factor into account. They usually average across age, often sample from a student population only (e.g., Li et al, 2016), and sometimes do not mention their participants' age at all (e.g., Bulkes and Tanner, 2017). Whether age affects the idiom vocabulary in a similar way as the single-word vocabulary is therefore an open question.…”
Section: Introductionmentioning
confidence: 99%
“…A significant main effect of phrase type was observed, [ = -0.026, SE = 0.012, t (164) β 9 Twenty-six native English speakers (MTurk workers) rated the literal plausibility of all phrases. The instructions given were identical to the literal plausibility instruction used in Bulkes and Tanner (2017) .…”
Section: Mandarin-english Bilingualsmentioning
confidence: 99%
“…Another relevant variable is final word predictability [5,16,17], which refers to the likelihood of providing a correct idiomatic completion in a fill-in-the-blank (cloze) task (e.g., estirar la ____ / Kick the ____). For example, the idiom "verse de higos a brevas" (e.g., to meet very rarely; literally: to meet from figs to figs) is fairly predictable in Spanish, given that an alternate completion is highly unlikely (e.g., verse de higos a manzanas; literally: to meet from figs to apples), and even semantically anomalous.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that sentences are comprehended faster and more accurately if they contain idioms that are familiar to the speakers rather than unfamiliar [5,9,19,20]. A related variable is the knowledge of the figurative meaning [6,8] or meaningfulness [5,6,16,21]. It refers to how well an individual knows the meaning of an idiomatic expression and it has been shown to be related with online reading idiom comprehension times [21].…”
Section: Introductionmentioning
confidence: 99%